Synthesis, equilibrium, and biological study of a C-7 glucose boronic acid derivative as a potential candidate for boron neutron capture therapy. (1st April 2022) - Muz, Barbara; Azab, Abdel Kareem; Confalonieri, Laura; Del Grosso, Erika; Fallarini, Silvia; Imperio, Daniela; Panza, Luigi
Graphical abstract: Highlights: Synthesis of a stable glucose derivative containing a boronic acid moiety on C-7. Metathesis reaction as tool for introducing boronic moiety into the sugar skeleton. High-resolution mass for studying equilibrium species in solution of boronic acid derivatives. Boron accumulation in D54 glioma cells and fibroblasts analyzed by ICP-MS. Abstract: The synthesis of d -glucoheptose derivative containing a boronic moiety is described herein. Starting from benzyl 6, 7-dideoxy-2, 3, 4-tri- O -benzyl-β-d - gluco -ept-6-enopyranoside, the introduction of the boronic acid was performed through a metathesis reaction by using MIDA vinyl boronic acid and the 2nd generation Grubbs catalyst. Hydrogenation led to the final product in only two reaction steps. This new sugar-containing boronic acid in the skeleton could mimic carbohydrate behavior and follow the glucose uptake in living cells. The in vitro toxicity tests performed in fibroblasts and glioma tumor cell lines showed minimal toxicity. Boron uptake measured using ICP-MS was minimal in fibroblasts, while in glioma cells showed a value of 6 ng of total boron accumulation per mg of cells, implying that compound 1a is able to accumulate selectively in the tumor tissues compared to normal.